Exploring University EFL Learners' Experiences in Using Podcasts for Listening and Vocabulary Development: Podcasts for Listening and Vocabulary Development - Mustofa Abdul Aziz Aziz; Ahmad Tauchid; Moh. Zainuddin; Mohammad Fatoni; Mustofa Abdul Aziz Aziz; Ahmad Tauchid; Moh. Zainuddin; Mohammad Fatoni (INTENS (International Journal of English Education and Linguistics), 2025)
This explanatory sequential mixed-methods study investigates university EFL learners' experiences with podcast-based learning for listening comprehension and vocabulary acquisition. The research addresses three key questions: (1) how learners utilize podcasts, (2) challenges encountered, and (3) effective learning strategies. Quantitative data collected from 20 participants revealed YouTube as the dominant platform (95%), with speech speed (65%) and accents (35%) as primary barriers. Qualitative interviews with 8 selected participants uncovered three adaptive strategies: segment repetition (55%), transcript utilization (50%), and vocabulary journaling. Analysis demonstrated significant improvements in listening proficiency (80% of users) and vocabulary retention (95%), particularly when podcasts incorporated scaffolding features. The study highlights the pedagogical value of podcasts as authentic input sources while emphasizing the need for speed-adjustable content, culturally familiar topics (preferred by 60%), and integrated learning supports. These findings contribute to understanding autonomous language learning in digital environments, suggesting that podcast effectiveness depends on strategic use rather than mere exposure. Practical implications include recommendations for educators to incorporate structured podcast activities and for developers to create leveled content with multimodal supports. The research bridges theoretical frameworks of comprehensible input with contemporary digital learning practices in EFL contexts